2009
DOI: 10.4161/auto.5.4.7760
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induced by 2-deoxy-D-glucose suppresses intracellular multiplication ofLegionella pneumophilain A/J mouse macrophages

Abstract: Legionella pneumophila Philadelphia-1 (Lp-1) can grow intracellularly in A/J mouse peritoneal macrophages (A/J Mphi). We previously reported that 2-deoxy-D-glucose (2dG), when added in macrophage culture medium, inhibited the intracellular multiplication of Lp-1 in A/J Mphi. We found that 1 mM of 2dG causes LC3-II-conversion that reflects an induction of autophagy and that 1 and 10 mM of 2dG induced apoptosis associated with caspase-4 activation. We therefore investigated whether 2dG-induced autophagy or apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…Indeed, we confirmed the ability of 2-DG to induce autophagy in cardiomyocytes (Fig. 6), consistent with findings in other cell types (63,64). Autophagy is the primary cellular pathway for lysosomal degradation and recycling of long lived proteins and organelles, which plays an extremely important role in cytoplasmic quality control and maintaining cellular homeostasis under both normal and path- ological conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, we confirmed the ability of 2-DG to induce autophagy in cardiomyocytes (Fig. 6), consistent with findings in other cell types (63,64). Autophagy is the primary cellular pathway for lysosomal degradation and recycling of long lived proteins and organelles, which plays an extremely important role in cytoplasmic quality control and maintaining cellular homeostasis under both normal and path- ological conditions.…”
Section: Discussionsupporting
confidence: 90%
“…2C), two pathways that negatively regulate autophagy. Thus, it is very likely that 2-DG could induce autophagy in cardiomyocytes as it did in other cell types (63,64). To test if 2-DG can indeed trigger autophagy in cardiomyocytes, we infected NRC with AdGFP-LC3 and then treated cells with 500 M 2-DG.…”
Section: -Dg Induced Autophagy In Neonatal Rat Cardiomyocytes-mentioning
confidence: 99%
“…When expression of the autophagy component ATG5 is silenced, L. pneumophila replication in A/J macrophages increases. Additionally, replication of L. pneumophila decreases slightly when autophagy is induced exogenously, suggesting that autophagy contributes to restriction of L. pneumophila replication (Matsuda et al, 2009). Under low MOI infection conditions where there is minimal induction of pyroptosis, it was revealed that the induction of autophagy dampens pyroptosis in response to L. pneumophila, and turnover of autophagosomes requires NAIP5, NLRC4, and caspase-1 (Byrne et al, 2013).…”
Section: Inflammasome Activation and Autophagymentioning
confidence: 99%
“…Proteins required for initiation of autophagosome formation, ATG7, and autophagosome maturation, ATG8, localize to the LCV during infection of these cells, suggesting that autophagy may play an antimicrobial role on the host response to Legionella [79]. Evidence in support of this hypothesis is provided by siRNA knockdown experiments in which the depletion of the critical autophagy factor ATG5 results in an increase in intracellular replication of Legionella during infection [76,80]. The manner in which this pathway is triggered, however, remains a mystery.…”
Section: Autophagymentioning
confidence: 99%